Representation and inclusion in public organization: evidence from the U.K. civil services - Andrews, Rhys; Ashworth, Rachel (2015)
Theories of workforce diversity in the public sector assume that organizations that are more representative of the population they serve are more likely to foster an inclusive work climate in which individuals from different sections of society can thrive. The authors examine this assumption by studying whether gender and minority ethnic representativeness are related to perceptions of inclusiveness and the experience of discrimination and bullying within U.K. civil service organizations. Findings suggest that gender representativeness and minority ethnic representativeness are both associated with an inclusive work climate, with each aspect of representativeness positively related to higher perceptions of inclusion and lower levels of discrimination and bullying. The theoretical and practical implications of the findings are discussed. - Reproduced.
Keywords: Civil service - Great Britain; Civil service